2000
DOI: 10.1007/s100380070022
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and chromosomal localization of the gene encoding TRAX, a Translin-associated factor X

Abstract: The TRAX gene encodes a Translin-associated 33-kDa protein partner, TRAX. The TRAX protein has extensive amino acid homology with Translin, and contains bipartite nuclear targeting sequences, suggesting a possible role in the selective nuclear transport of Translin lacking any nuclear targeting motifs. In the present study, genomic clones of the human TRAX gene were isolated to determine the complete genomic organization. The genomic structure of the human TRAX gene was similar to that of the human Translin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…One clone product gave specific activation with the translin bait. Its nucleotide sequence revealed an open reading frame encoding a protein of 290 amino acids with a predicted molecular weight of 33 kDa, and the encoded protein was named TRAX . TRAX exhibits extensive amino acid homology with translin.…”
Section: Identification and Characterization Of Traxmentioning
confidence: 99%
“…One clone product gave specific activation with the translin bait. Its nucleotide sequence revealed an open reading frame encoding a protein of 290 amino acids with a predicted molecular weight of 33 kDa, and the encoded protein was named TRAX . TRAX exhibits extensive amino acid homology with translin.…”
Section: Identification and Characterization Of Traxmentioning
confidence: 99%
“…To identify the location at which TRAX exerts its protective effect, we created a TRAX mutant that lacks the nuclear localization signal (NLS; amino acids [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and is fused to a V5-tag (designated ΔNLS-V5). As shown in Figure 3d, ΔNLS-V5 was located mainly in the cytoplasmic region.…”
Section: Development Of a Trax-null Mouse Model Using The Gene-trap Mmentioning
confidence: 99%
“…18 TRAX and Translin share extensive amino acid homology and form heterodimers to mediate biological functions, including chromosomal translocations, genome stability regulation, dendritic trafficking of brain-derived neurotrophic factor mRNA, spermatogenesis and neuronal development. [19][20][21][22] Independent to Translin, TRAX alone regulates axonal regeneration 23 and rescuing impaired neuronal differentiation caused by p53 blockade. 24,25 In response to DNA damage, TRAX interacts directly with C1D, a nuclear matrix protein participating in DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Using inhibitors of PKA or GSK3beta to test the role of these signaling pathways in mediating dissociation of trax from A 2A R, they found that: 1) inhibition of PKA blocks the ability of A 2A R stimulation to phosphorylate GSK3β, and 2) GSK3β inhibition triggers dissociation of trax from the A 2A R. Further examination of the interaction between GSK3β and trax revealed that they co-precipitate along with Disrupted-in-Schizophrenia 1 (DISCI), a protein known to interact with GSK3P [5]{Chien, 2018 #6}. Detection of a physical interaction between DISCI and trax is of particular interest because these two proteins are encoded by two genes (namely DISCI and TSNAX) that are located adjacent to each other on human chromosome 1 in a region that has been implicated in major mental disorders (such as schizophrenia, autism, depression, and bipolar disorder) [29][30][31][32][33][34].…”
Section: Role Of Trax In the Nucleus: Dna Repairmentioning
confidence: 99%